New treatment approaches for the management of Alzheimer's disease - Abhishek; Sourav Pahwa (Journal of Applied Pharmaceutical Research, 2022)
This assessment is mainly concerned with the new treatment approaches for the management of Alzheimer’s disease and how these procedures can be beneficial for patients suffering from such diseases. With various other brain diseases, the number of Alzheimer’s disease cases is also increasing day by day in the world. So, it has become very important to be aware of the various new methods for the treatment of Alzheimer’s disease. The new treatment methods that are been used for the treatment of such brain disorders are found to be highly beneficial, as various new therapies and methods are being discovered for the treatment of such brain diseases. The various medications that are being used for the treatment of such diseases are beneficial only when taken under proper guidance and amount. Various precautions are very necessary during the treatment of such diseases, which can be helpful in the treatment. These treatment procedures may vary from person to person depending on their age factor and health.